A relação entre discurso e identidade na revista vogue Brasil - Lessa, Monique de Mesquita (2018)
This research is motivated by an interest in investigating critically how magazines construct identities in their discourses. It is situated in the current scientific debate about the relation between the concept of discourse, from linguistics, and the concept of identity, from the social sciences; and it is embedded in the field of Critical Discourse Analysis (CDA). The focus in this investigation is the magazine Vogue Brasil, which is recognized as normalizing life styles and ways of existing (ELMAN, 2008; NOVELLI, 2009). The main purpose here is to analyze the discursive construction of social and cultural identities. The concepts and considerations about identities proposed by Hall (2006), Larraín (2001) and Castells (1999) are related to the notions of discourse that are examined in the field of CDA by Magalhães (2006, 2010, 2011), van Dijk (2009), and Fairclough (2001, 2003). The consumer practice and the commodification process of this magazine are taken as mediating this relation, and, therefore, they also contribute to the debate about discourse and identity. The selected corpus for the analysis corresponds to 20 stories published in Vogue Brasil from January to June 2016, which are analyzed with a focus on intertextuality and interdiscursivity proposed by Magalhães (2010) and Fairclough (2001, 2003) as categories to analyze the identificational meaning of discourse. In addition, the contributions about multimodality that were developed by Kress and van Leeuwen (2006) are also adopted for the analysis of images and graphic elements which are parts of the stories. Consequently, the discourses that are materialized in this magazine are also investigated. The results of the analysis suggest that commodified identities are constructed (LIRA, 2015), while readers exert a strong influence in the choices and in the construction of the magazine discourses, establishing a dialectical relation that is also configured as a dispute for the control of the identities and discourses manifested.